Women's experiences of sexuality after spinal cord injury: a UK perspective. Issue 11 (November 2018) - Thrussell, Helen; Coggrave, Maureen; Graham, Allison; Gall, Angela; Donald, Michelle; Kulshrestha, Richa; Geddis, Tracey
Abstract Study design Cross-sectional phenomenological qualitative study. Objectives To investigate women's experience of sexuality after spinal cord injury (SCI) with a focus on rehabilitation and manging practical impact. Setting Women with SCI living in the community in United Kingdom (UK). Methods Participants were recruited via three UK SCI centres, ensuring tetraplegia, paraplegia and cauda equina syndrome representation. Single semi-structured interviews exploring individual's experiences around sexuality following SCI were recorded and transcribed for thematic analysis. Results Twenty-seven women aged 21–72 years, sexually active since SCI were interviewed, each lasting 17–143 min (mean 55 min). Six key themes emerged: physical change, psychological impact, dependency, relationships and partners, post injury sexual life and sexuality rehabilitation. Conclusions Sexuality remains an important, valued aspect of female identity following SCI; sexual activity continues and though altered remains enjoyable and rewarding. Sexuality rehabilitation should commence early, preparing women for altered sexual sensation, disclosure of altered sexual function to partners, and encouraging early self-exploration. Techniques optimising continence management in preparation for and during sex should be taught. Participants identified a need for women-only education and support groups, increased peer support, self-esteem, communication and social skills training and even fashion advice and pampering sessions during rehabilitation. Support and education for partners are needed. Staff require support to be knowledgeable and confident in addressing women's sexuality needs. Use of the Ex-PLISSIT model for psychosexual support could help staff to better meet these needs.